Mathematical Logic Establishment for Automated Trash Controlling in Carding Machine - Islam, Md. Redwanul; Zubaer, Numan; Iqbal, Tareq; Khan, Md. Abir (European Scientific Journal, ESJ, 2019)
In this paper, it is intended to establish a mathematical logic for the purpose of removal of trash in an automatic way and removal of trash will refer to the cleaning process of carding machine. But the selection of degree of cleaning has to be optimum considering other process factors like fiber loss, fiber rupturing, neps generation etc. Higher degree of cleaning causes higher degree of fiber loss. And in spinning mill, fiber loss means money loss as raw cotton purchasing cost consumes 50% to 60% of total manufacturing cost of yarn in terms of Bangladesh. Alongside, fiber loss is affected the cleaning system because the system is designed for fiber cleaning, not for fiber loss. So, it is necessary to measure the performance of the system. For this purpose, we have chosen two terms, ‘Cleaning Efficiency (C.E.)’ to measure the degree of cleaning & ‘Effective Cleaning (E.C.)’ to measure the performance of the system. In this paper, it is intended to describe a relationship between these two terms, graphical expression of the individuals, a way to calculate the force applied by mechanical means and the force required to clean. The ultimate result of this project is to find the relationship between the surface speed of taker-in and the trash weight of output material.